The nonfarm sector and rural development: review of issues and evidence - Islam, Nurul (International Food Policy Research Institute, 1997)
In most developing countries, the rural labor force is growing rapidly, but rural employment opportunities are dwindling. This paper brings together empirical evidence on the nonfarm sector and analyzes policies for its future development. It examines the linkages between the farm and nonfarm sectors and between the nonfarm sector and urban enterprises, and considers ways the government can promote rural employment.